Eighteen cases of renal aneurysms: Clinical retrospective analysis and experience of endovascular interventional treatment - Lu, Tao; Lin, Bin; Zhang, Yan-ping; Zhang, Jian-hui; Luo, Jie-Wei; Tang, Yi; Fang, Zhu-Ting (Frontiers in Surgery, 2023)
Background: Development of endovascular interventional techniques gradually replaced traditional open surgery and has become the preferred treatment for renal aneurysms. This study aimed to analyze the clinical characteristics of renal artery aneurysm (RAA) and the safety and efficacy of intravascular interventional treatment. Materials and Methods: We retrospectively analyzed the clinical characteristics and imaging data of 23 aneurysms in 18 patients with RAA. The technical success rate, complication rate, mortality rate, reintervention rate, and use of embolization materials were evaluated. Results: In 18 patients with RAA (age, 3272 years; average age, 52.2 ± 11.2 years), a total of 23 aneurysms were found (diameter 0.55.5 cm; average diameter 2.2 ± 1.4 cm). Among them, 11 cases (61.1%) were discovered accidentally, and the remaining patients were diagnosed due to the following major complaints: four cases (22.2%) presented low back pain, two (11.1%) were due to high blood pressure, and one (5.5%) had low back pain with gross hematuria. A total of 14 aneurysms in 13 patients received endovascular interventional therapy. The technical success rate of 13 patients with renal aneurysms was 100%. Three of the 18 patients were lost to follow-up, and the remaining were followed up for 489 months. There was no recurrence of the aneurysm or displacement of the stent or coil. Conclusion: Endovascular treatment for RAA has a high success rate, low complication rate, and low reintervention rate. It has the advantage of less trauma and is flexible and more targeted for different types of renal aneurysms.